Sex Difference Impacts on the Relationship between Paraoxonase-1 (PON1) and Type 2 Diabetes - Valentina Rosta; Alessandro Trentini; Angelina Passaro; Giovanni Zuliani; Juana Maria Sanz; Cristina Bosi; Gloria Bonaccorsi; Tiziana Bellini; Carlo Cervellati (MDPI AG, 2020)
Type-2 diabetes (T2D) and its cardiovascular complications are related to sex. Increasing evidence suggests that paraoxonase 1 (PON1) activity, an antioxidant enzyme bound to high-density lipoproteins (HDL), is implicated in the onset and clinical progression of T2D. Since we previously showed that PON1 is a sexual dimorphic protein, we now investigated whether sex might impact the relationship between PON1 and this chronic disease. To address this aim, we assessed PON1 activity in the sera of 778 patients, including controls (women, n = 383; men, n = 198) and diabetics (women, n = 79; men = 118). PON1 activity decreased in both women and men with T2D compared with controls (p < 0.05 and p > 0.001, respectively), but the change was 50% larger in the female cohort. In line with this result, the enzyme activity was associated with serum glucose level only in women (r = −0.160, p = 0.002). Notably, only within this gender category, lower PON1 activity was independently associated with increased odds of being diabetic (odds ratio (95% Confidence interval: 2.162 (1.075-5.678)). In conclusion, our study suggests that PON1-deficiency in T2D is a gender-specific phenomenon, with women being more affected than men. This could contribute to the partial loss of female cardiovascular advantage associated with T2D.